Determination of Policy Development Priorities in Integrated Waste Management Site at Bantargebang Bekasi - Sukwika, Tatan; Sulistyadi, Yohanes; B Sukamdani, Nugroho (KnE Social Sciences, 2023)
The garbage problem from DKI Jakarta in the integrated waste management (IWM) site at Bantargebang Bekasi is still interesting for study. The existing studies generally relate to water, soil, air pollution, social conflict, institutional, and area expansion. This study focuses on determining priority strategies for policy development at the IWM Site. The analytical hierarchy process (AHP), analysis method was used to measure priority options regarding integrated Jakarta waste management policies at the IWM site. They collected data by interviewing experts, primary data sources, and other information from various related agencies. The existing condition performance graphs and dynamic sensitivity results show that alternative strategies for improving human resources are a priority for policy development at the IWM Site. The next priority in a row is facilities and infrastructure development, waste utilization management regulations, and increased stakeholder cooperation and coordination. The conclusion is that the policy to raise human resources is most relevant to the current needs of the implementing management unit of the IWM site. It is recommended that further studies related to risks and disasters from the existence of technology-based waste processing have the potential to cause new problems from environmental and social aspects. Keywords: AHP, alternative priority, human resources, integrated waste management